Anti-erosive profile of an experimental 5% SnCl₂ varnish containing different concentrations of NaF - Alencar, Cristiane de Melo [UNESP]; Ribeiro, Mara Eliane Soares; Zaniboni, Joissi Ferrari [UNESP]; Leandrin, Thais Piragine [UNESP]; Silva, Aryvelto Miranda [UNESP]; Campos, Edson Alves de [UNESP] (FapUNIFESP (SciELO), 2022)
This in vitro study evaluated the anti-erosive effect of an experimental varnish containing 5% stannous chloride (SnCl₂) associated with different concentrations of NaF (NaF-free, 2.5% NaF, or 5.2% NaF) on bovine enamel and root dentin. One hundred samples were pre-eroded (0.3% citric acid, pH 2.6, 10 min) and randomized into five groups (n=10 for each substrate): Negative control - milli-Q water; NaF-free - Experimental varnish SnCl₂-free and NaF-free; 2.5 NaF - Experimental varnish 5% SnCl₂ associated with 2.5% NaF; 5.2 NaF: Experimental varnish 5% SnCl₂ associated with 5.2% NaF and positive control - Commercial varnish containing 5% NaF (Duraphat). After the varnishes were applied, the erosive and abrasive challenges were carried out for five days. Loss of tooth structure (TSL) was determined by optical profilometry, and the loss of calcium (ΔCa2+) using atomic absorption spectroscopy. Dentin analysis was also performed by SEM. A one-way ANOVA/Bonferroni test was performed to analyze the data (α=0.05). The experimental 2.5 NaF and 5.2 NaF groups showed greater effectiveness in preventing TSL when compared to the other groups (p <0.05), regardless of the substrate. In addition, these groups showed lower loss in Ca2+ content when compared to the other groups (p <0.05), for enamel and dentin. Dentin showed greater TSL and ΔCa2+ loss when compared to enamel in all treatments (p <0.05). The 5.2% and 2.5% NaF-containing experimental varnishes showed promising results in both, the prevention of TSL and the loss of Ca2+, regardless of the substrate studied.